Carnivore conservation in practice: replicated management actions on a large spatial scale. Issue 1 (30th January 2013) - Angerbjörn, Anders; Eide, Nina E.; Dalén, Love; Elmhagen, Bodil; Hellström, Peter; Ims, Rolf A.; Killengreen, Siw; Landa, Arild; Meijer, Tomas; Mela, Matti; Niemimaa, Jukka; Norén, Karin; et al.
Summary More than a quarter of the world's carnivores are threatened, often due to multiple and complex causes. Considerable research efforts are devoted to resolving the mechanisms behind these threats in order to provide a basis for relevant conservation actions. However, even when the underlying mechanisms are known, specific actions aimed at direct support for carnivores are difficult to implement and evaluate at efficient spatial and temporal scales. We report on a 30‐year inventory of the critically endangered Fennoscandian arctic fox Vulpes lagopus L., including yearly surveys of 600 fox dens covering 21 000 km2. These surveys showed that the population was close to extinction in 2000, with 40–60 adult animals left. However, the population subsequently showed a fourfold increase in size. During this time period, conservation actions through supplementary feeding and predator removal were implemented in several regions across Scandinavia, encompassing 79% of the area. To evaluate these actions, we examined the effect of supplemental winter feeding and red fox control applied at different intensities in 10 regions. A path analysis indicated that 47% of the explained variation in population productivity could be attributed to lemming abundance, whereas winter feeding had a 29% effect and red fox control a 20% effect. This confirms that arctic foxes are highly dependent on lemming population fluctuations but also shows that red foxes severely impact the viability of arctic foxes. This study also highlights the importance of implementing conservation actions on extensive spatial and temporal scales, with geographically dispersed actions to scientifically evaluate the effects. We note that population recovery was only seen in regions with a high intensity of management actions. Synthesis and applications. The present study demonstrates that carnivore population declines may be reversed through extensive actions that target specific threats. Fennoscandian arctic fox is still endangered, due to low population connectivity and expected climate impacts on the distribution and dynamics of lemmings and red foxes. Climate warming is expected to contribute to both more irregular lemming dynamics and red fox appearance in tundra areas; however, the effects of climate change can be mitigated through intensive management actions such as supplemental feeding and red fox control.